Balance and muscle strength tests in patients with osteoporotic vertebral fractures to develop tailored rehabilitation programs - Ekaterina V Makarova; Larisa A Marchenkova; Mikhail A Eryomushkin; Elena M Styazkina; Ekaterina I Chesnikova (PAGEPress Publications, 2020)
Authors perform a cross-sectional study of functional abilities of the patients with osteoporotic VF. Trunk muscle isometric strength and balance impairments were estimated. The development of osteoporotic VFs is associated with a significant decrease in strength of all the body muscles, especially the deep spinal stabilization system (TE, TF), where the VFs contribute to inappropriate distribution of back muscle strength with TE:TF ration of 1:1 instead of 3:2, observed both normally and in patients with uncomplicated osteoporosis. There is also a deterioration of stabilometry and functional balance assessment tests in patients with pathological VFs, which indicates abnormalities of both static and dynamic balance. The obtained data should be taken into account when developing rehabilitation programmes for patients with osteoporosis who have suffered compression VFs.